2018
DOI: 10.3390/insects9040166
|View full text |Cite
|
Sign up to set email alerts
|

Not Led by the Nose: Volatiles from Undamaged Eucalyptus Hosts Do Not Influence Psyllid Orientation

Abstract: Psyllids (Hemiptera: Psylloidea) are small sucking insects with high host plant specificity. Despite the primitive olfactory system of psyllids, some species have been suggested to rely on host plant volatiles (HPVs) for seasonal migration between summer deciduous hosts and winter coniferous hosts. Similarly, enhanced attraction of psyllid vectors has been observed as a result of the manipulation of host odors by plant pathogens. As yet, there are no studies of olfaction in psyllids that utilize evergreen euca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
0
9
1
Order By: Relevance
“…Species such as Cacopsylla bidens (Šulc, 1907), the pear psyllid, has been observed to respond to volatile cues from both the host plant and conspecifics using olfactometric and electroantennographic assays (Soroker et al 2004). On the contrary, Farnier et al (2018) did not find patterns of positive chemotaxis to volatiles of undamaged leaves of Eucalyptus L'Hér on different Eucalyptus-feeding psyllids. However, little is still known regarding the preference of T. erytreae for olfactory stimuli emitted by different host plants.…”
Section: Introductioncontrasting
confidence: 63%
“…Species such as Cacopsylla bidens (Šulc, 1907), the pear psyllid, has been observed to respond to volatile cues from both the host plant and conspecifics using olfactometric and electroantennographic assays (Soroker et al 2004). On the contrary, Farnier et al (2018) did not find patterns of positive chemotaxis to volatiles of undamaged leaves of Eucalyptus L'Hér on different Eucalyptus-feeding psyllids. However, little is still known regarding the preference of T. erytreae for olfactory stimuli emitted by different host plants.…”
Section: Introductioncontrasting
confidence: 63%
“…Thus, it seems that modulation of VOCs directed to disrupt pathogen–host plant interactions is a viable approach for pest management that would have no residual effects on the environment. Psyllid species rely on olfactory cues to find their hosts, but evidences are difficult to obtain by laboratory bioassays, as physiological stage, light intensity, and the presence of visual cues influence their behavior ( Nissinen et al, 2008 ; Wenninger et al, 2009 ; Farnier et al, 2018 ). However, different studies indicated that psyllids respond positively to their host odors, for example, the common pistachio psyllid Agonoscena pistaciae is attracted to volatiles of pistachio leaves ( Ghamari et al, 2018 ) and Cacopsylla pruni to those of apricot ( Andrianjaka-Camps et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Why C. longicauda was not attracted to ACP lures, which are derived from the plant volatiles of fresh citrus growth (Setamou et al, 2018), remains unknown. The congeneric Ctenarytaina eucalypti was repelled by volatiles produced by damaged host plant leaves (Farnier et al, 2018), and perhaps C. longicauda is similarly sensitive, being repelled by the concentrations or ratios of semiochemical in the ACP lures.…”
Section: Discussionmentioning
confidence: 99%